Turning on the we-mode: a systematic review on joint action principles for promoting collective pro-environmental engagement - Sarabi, Shahryar; Gillebaart, Marleen; de Ridder, Denise (Frontiers in Psychology, 2025)
Collective pro-environmental engagement of communities is vital for addressing climate change through system-wide transformations. To promote such engagement, individuals must go beyond their immediate personal interests, requiring activation and promotion of pro-social behaviors. In this review we aimed to explore joint action as a way to “boost” collective action approaches beyond specific frontrunner groups. In recent years, joint action (i.e., social interaction whereby individuals coordinate their actions to bring about a change in the environment.) has received significant attention as an approach that can bring about various pro-social behaviors. We conducted a systematic literature review to identify the pro-social outcomes associated with joint action and discuss its potential to promote collective pro-environmental engagement. Our analysis revealed two types of pro-social behaviors: those related to group functioning (togetherness, perspective taking, and cooperative behavior) and those tied to group performance (commitment, agency). These behaviors can be effectively promoted by joint action, as witnessed by medium to large effect sizes. We therefore argue that these findings offer a promising pathway for leveraging joint action as a means to enhance collective pro-environmental engagement across a broad segment of the population, and ultimately provide effective climate governance strategies.